Inversion of shallow seabed structure and geoacoustic parameters with waveguide characteristic impedance based on Bayesian approach - Zhu, Hanhao; Xue, Yangyang; Ren, Qunyan; Liu, Xu; Wang, Jiahui; Cui, Zhiqiang; Zhang, Shu; Fan, Huili (Frontiers in Marine Science, 2023)
Underwater acoustic technology is essential for ocean observation, exploration and exploitation, and the development of this technology is based on an accurate predicition of underwater acoustic wave propagation. Geoacoustic parameters are essential for predicting the acoustic wave propagation characteristics, especially in shallow sea environments. To obtain more accurate inversion results for these parameters, this study presents an inversion method using the waveguide characteristic impedance based on the Bayesian approach. In the inversion, the vertical waveguide characteristic impedance, which is the ratio of the pressure over the vertical particle velocity, is set as the matching object. The nonlinear Bayesian theory is used to invert the seabed structure, the sound speeds, the densities, and the sound speed attenuations in seabed layers, and the uncertainty of the inversion result is also be analyzed. Numerical studies have proved that the vertical waveguide characteristic impedance is more sensitive to the above geoacoustic parameters than that of single acoustic pressure or single vertical particle velocity, and the error of simulation inversion is within 3%. The sea experiment‘s inversion shows that the seabed layered structure and geoacoustic parameters can be accurately determined by this method. The root mean square between the vertical waveguide characteristic impedance and the measured impedance is 0.38dB, and the inversion results accurately represent the seabed characteristics inf the experimental sea area.